The Impact of Fish Processing Training Program on Community Independence in Kampung Mandar Banyuwangi - wulandari, sisi (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
The development of the Marina Islands has made it difficult for the people of Mandar Village to find fish in the sea considering that almost all of the people of Mandar Village work as fishermen. Therefore, the Banyuwangi Regency government provided a solution by holding an entrepreneurship training program in the form of processing products from fish raw materials for the people of Mandar Village. The aim of this research is to describe the impact of the fish processing training program on the independence of the people of Kampung Mandar Banyuwangi using a qualitative approach method. The location for this research was chosen using a purposive area technique and is located in Mandar village, Banyuwangi district. This research data collection technique uses observation, interview and documentation techniques. From this research, research results were obtained which show that the people of Mandar Village are able to be economically independent by having new skills and knowledge that they have, apart from that, thanks to the motivation and responsibility they carry out as entrepreneurs of processed fish products, they are able to consistently develop their business until now.